Overconfidence, sexual health awareness and sexual health risk among young female users of sexual health clinics. (2015) - Dunne, L.; McCann, M.; Millen, S.; Wilson, J.; Macdonald, G.
Highlights: We surveyed young people in two sexual health clinics in Northern Ireland. Analysis revealed three typologies of sexual health competence. Self-rated sexual health competence may not match actual sexual health knowledge. Poor knowledge may increase risk of poor sexual health outcomes for young people. This work has implications for sexual health education programmes. Abstract: This study explored the patterning of young people's sexual health competence, and how this relates to sexual health outcomes. A survey of 381 young people attending two sexual health clinics in Northern Ireland was carried out between 2009 and 2010. Latent profile analysis of self-rated decision making, self-rated sexual health knowledge, and knowledge of sexually transmitted disease questionnaire scores was used to determine typologies of sexual health competence. Analysis revealed three categories of sexual health competence and explored their association with other behaviours and social characteristics. Young people's subjective opinion of their sexual health competency, when not matched with a corresponding knowledge of sexual health, could place people at an increased risk of poor sexual health outcomes. Greater levels of peer pressure to have sex and early sexual debut were associated with poorer sexual health knowledge. This finding warrants further investigation, as the importance of self-perceived competence for sexual health screening and education programmes are considerable.